The Analysis of Compliment Strategies in a Movie Entitled The Spectacular Now - Arimbi, Rafika (Universitas Sebelas Maret, 2021)
This research focuses on what kind of compliment and compliment responses in a movie entitled The Spectacular Now. This paper tries to find out the types of compliment’s topics, to reveal the functions of each type of compliment’s topics and to figure out the types of compliment responses employed by the characters in the movie entitled The Spectacular Now. This research is descriptive qualitative research. This research uses a pragmatic approach. The technique used is purposive sampling, meaning that the researcher took all of dialogues containing giving and responding compliments as data. The results show that first the most common topic of compliment used by the characters is the ability topic. Following the Wolfson’s theory, there are five functions found in the movie. They are to express admiration or approval, to maintain rapport, to modify sarcasm, to encourage, and to give positive evaluation for someone. Furthermore, there are eight compliment responses found in the movie based on Herbert’s classification. They are appreciation token, no-acknowledgement, comment acceptance, question, scale down, disagreement, request, and return. Based on the analysis, the most widely used is appreciation token with verbal acceptance.